FROM LOCAL CHAMPION TO GLOBAL PLAYER: A SWOT ANALYSIS AND STRATEGIC ROADMAP FOR ELEVATING BANK SYARIAH INDONESIA INTO THE TOP 3 GLOBAL ISLAMIC BANK BY 2030 - Indah K, Agus Tri; Al Rasyid, Harun; Sazly, Syukron (Dynamic Management Journal, 2025)
Bank Syariah Indonesia (BSI) is the result of a merger between three national Islamic banks and holds strong potential to become a global player. However, as of 2024, BSI remains outside the top three global Islamic banks, with total assets of USD 25 billion, lagging behind Al Rajhi Bank, KFH, and DIB. This study aims to analyze BSI's position using a SWOT approach and to evaluate its performance through RGEC indicators (Risk Profile, Good Corporate Governance, Earnings, Capital) and the Global Composite Index. A descriptive qualitative method was employed, including literature review, financial report analysis (2020–2024), and benchmarking against 10 global Islamic banks. Results show BSI is in a sound financial position, with an NPF of 2.2%, ROA of 1.4%, and CAR of 19.3%, but has a relatively low Global Composite Index score (52/100) compared to Al Rajhi (89/100) and KFH (84/100). Recommended strategies include regional expansion, digital transformation, and strengthening capital through global investors. Limitations include restricted access to internal data and comparative benchmarking.